A Collaborative Wireless Access to On-Demand Services. (10th February 2008) - Naor, Zohar
Abstract : A collaborative access scheme that exploits the broadcast nature of the wireless communication in order to achieve multicast content delivery is presented in this paper. The key idea is that individual clients requesting for the same content can collaborate and share the same data channel. As opposed to broadcasting, this method enables the clients to determine online the delivered content, and thus supports on-demand services. On the other hand, a multicast content delivery is much more efficient than a unicast content distribution, which must use a dedicated data channel per each and every client. This method is particularly suitable for sessions having a long-time duration, for applications in which clients can subscribe to ahead of time, and for applications in which the clients receive the same information simultaneously. A multicast content distribution increases the network service throughput in terms of the expected number of clients served simultaneously, and therefore it offers a reduced waiting time for content delivery at highly loaded time periods. It is shown that the problem of maximizing the efficiency of distributing a content in a wireless network is NP-hard. An approximation algorithm is therefore used, that for any0 < ε < 1 finds an approximation solution with a relative accuracyε . The proposed method does not require any hardware modification on the network equipment. Thus, it can be easily implemented.